Correlation between cervical vertebral bone age and mandibular growth potential in a Javanese population: Korelasi antara cervical vertebral bone age dengan potensi pertumbuhan mandibula pada populasi suku Jawa - Marsellina Iduberga Mening Ibau; Annisa Putri; Basma Rosandi Prakosa; Raden Aditya Wisnu Wardhana (Makassar Dental Journal PDGI Makassar, 2026)
Assessment of mandibular growth potential is important in orthodontic treatment planning. Bone age, such as cervical vertebral bone (CVB) age, is consider-ed more accurate than chronological age in assessing skeletal maturation. This article discusses the correlation between CVB and mandibular growth poten-tial (MGP) in the Javanese population, through a correlative analytical study with a cross-sectional design, using 20 digital lateral cephalometric radiographs of Javanese patients aged 8-20 years. CVB measurements were performed using the Mito method, and MGP was calculated using a regression formula. At the initial stage, the mean CVB was 10.21 years, and MGP was 10.75 mm. At the final stage, CVB increased to 16.33 years, and MGP decreased to -1.53 mm. Pearson's test showed a significant negative correlation between CVB and MGP, Sig = 0.000 (p<0.05). It was concluded that there is a correlation bet-ween CVB and MGP in the Javanese population.